Application of natural fibre composite in the aviation industry: a review - Zuhair, M. R. M.; Hamdan, A.; Irfan, A. R. (FAZ Publishing, 2020)
The evolution in aviation industry continues to evolve in this current era. The aviation industry is engaged in the research, development and manufacturing of flight vehicles. The critical item such as the propulsion systems, avionics system, operating and maintenance of flight vehicle are rigorously improved year by year. The interior components of aircraft are gaining serious attention in replacing the synthetic fibre with natural fibre composite material. The researchers conducted are mainly for civil, security and transportation. However, the focus on aircraft interior still immature and need further investigation. Therefore, this paper is reviewing the potential of natural fibre in the aviation industry.